2023
DOI: 10.3390/healthcare11010142
|View full text |Cite
|
Sign up to set email alerts
|

Early Educational Interventions to Prevent Gender-Based Violence: A Systematic Review

Abstract: Background: Gender-based violence is a worldwide public health problem that is increasingly occurring at younger ages. This investigation aims to analyze effective interventions to prevent and to face gender-based violence beginning in early childhood in order to ensure quality education for all children through violence-free schools. Methods: This research has conducted a systematic review of interventions that have demonstrated a positive impact on the prevention and reduction of gender-based violence from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Evidence from previous studies has shown that most have concentrated on the ability to minimise or decrease GBV, especially domestic violence, with fewer studies focused on the role of economic empowerment and emotional violence (Bhana et al 2021;Eger 2021;Nunbogu and Elliott 2022;Montserrat et al 2022;del Mar Rodas-Zuleta et al 2022;Freijomil-Vázquez et al 2022). Another strand of studies focused on the micro-level (Bashford-Squires et al 2022;Tsai 2022;Okpara and Anugwa 2022;Mcilongo and Strydom 2021), while other studies carried out systematic reviews (Keith et al 2022;Sabri et al 2022; van Daalen et al 2022;Villardón-Gallego et al 2023;Mbukanma and Strydom 2021). Further studies concentrated on health, music, and socioeconomic issues such as sexuality, water, sanitation, and hygiene (Nunbogu and Elliott 2022;Philbrick et al 2022;Zhou et al 2022;Mahamid et al 2022;Raftery et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence from previous studies has shown that most have concentrated on the ability to minimise or decrease GBV, especially domestic violence, with fewer studies focused on the role of economic empowerment and emotional violence (Bhana et al 2021;Eger 2021;Nunbogu and Elliott 2022;Montserrat et al 2022;del Mar Rodas-Zuleta et al 2022;Freijomil-Vázquez et al 2022). Another strand of studies focused on the micro-level (Bashford-Squires et al 2022;Tsai 2022;Okpara and Anugwa 2022;Mcilongo and Strydom 2021), while other studies carried out systematic reviews (Keith et al 2022;Sabri et al 2022; van Daalen et al 2022;Villardón-Gallego et al 2023;Mbukanma and Strydom 2021). Further studies concentrated on health, music, and socioeconomic issues such as sexuality, water, sanitation, and hygiene (Nunbogu and Elliott 2022;Philbrick et al 2022;Zhou et al 2022;Mahamid et al 2022;Raftery et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%